FORMULATION OF SUSTAINED RELEASE CORE AND COAT TABLETS OF LOVASTATIN AND OLEANOLIC ACID: AN IN VITRO AND IN VIVO ANALYSIS - SATISH V. MANDAVE; NARENDRA KUMAR PANDEY; SACHIN KUMAR SINGH; BIMLESH KUMAR; SAURABH SINGH; DILEEP SINGH BAGHEL (Asian Journal of Pharmaceutical and Clinical Research, 2025)
Objectives: This research aimed to develop core and coat tablets to enhance the therapeutic efficacy of antilipidemic drugs for treating high cholesterol and triglyceride levels in the blood. Methods: The core and coat tablets were formulated using a combination of two antilipidemic drugs: Lovastatin (LV) and oleanolic acid (OA). LV was incorporated into an immediate-release (IR) layer with various superdisintegrants, while OA formulated into extended-release layer with hydroxypropyl methylcellulose K100. Results: The core and coat tablets were evaluated for the release profiles of both layers, and excipients were optimized. The IR layer of LV achieved complete release within 60 min, while the release of OA was sustained for up to 12 h. Among the formulations tested, LV9 (95.23%) for immediate release, and OA1 (97.13%) for sustained release, were found to be most suitable when scaled at the desired drug release up to 30 min and 12 h, respectively. Stability studies demonstrated that the optimized formulation remained stable without any degradation for 6 months. Pharmacokinetic and pharmacodynamic studies conducted in rabbit models examined the effects of LV/OA tablets on lipid profiles and body weight. Obesity was induced in the rabbits through a high-fat diet. Conclusion: The core and coat LV/OA tablets demonstrated significant efficacy in reducing lipid levels and mitigating weight gain compared to the control group.